Menalar Formalitas Corporate Social Responsibility dengan Perspektif Institutional Theory - Putra Umar Sakka, Gjosphink (E-Jurnal Akuntansi; Vol 30 No 6 (2020), 2020)
Theory of Corporate Social Responsibility (CSR) has always been associated with the concept of rights and responsibilities and the concept of sustainability. The theory is indeed appropriate to see the company's initiative to do CSR with the company's record in a condition of good financial performance. The problem here is that if a company has not been able to meet the demands of its target profit to shareholders, then there the applicable CSR rules are only seen as a formality without the essence of the initial CSR objectives themselves. This article aims to propose an institutional theory to add literacy theory to CSR in accordance with the case. Keywords: Formality; Corporate Social Responsibility; Institutional Theory.